A Study Of Mental Health And Life Skill Awareness Among Higher Secondary Students - Manvita Shivdas Khairnar, Dr. Priya Narendra Kurkure (International Journal of Advanced Research and Multidisciplinary Trends (IJARMT), 2025)
The present study investigates the relationship between mental health and life skill awareness among higher secondary students in Dhule city, Maharashtra. Adolescence is a critical developmental stage characterized by emotional fluctuations, academic pressure, and identity formation, making mental health a significant concern. Life skills such as communication, decision-making, problem-solving, and emotional regulation play a vital role in promoting psychological well-being during this phase. The study was conducted on a sample of 50 higher secondary students selected from various junior colleges in Dhule city using a stratified random sampling technique. A structured questionnaire was used to assess students’ life skills and mental health status. The findings revealed that while students demonstrated moderate levels of communication and decision-making skills, significant deficiencies were observed in stress management, emotional regulation, and real-life problem-solving abilities. A large proportion of students reported experiencing academic stress, anxiety during examinations, and difficulty maintaining emotional balance. The study also highlighted gender differences, with female students showing higher emotional awareness and male students exhibiting relatively better confidence in decision-making. Overall, the results emphasize the need for integrating life skills education with mental health awareness programs at the higher secondary level. The study recommends the inclusion of structured life skill training, counselling services, and stress management interventions to enhance students' psychological well-being and prepare them for future academic and life challenges.